Análise comparativa do desempenho de brocas de aço rápido AISI M2 revestidas com SiO2 pelo processo sol-gel na furação do ferro fundido nodular - Natália Fernanda Santos Pereira (2017)
Among the manufacturing processes, the machining stands out mainly with the technological innovations applied to this field, specially, with the target of increasing the life of the tool. The applications of coatings in cutting tools have contributed to this gain, besides providing the increase of productivity. On this purpose, the behavior of drills in High Speed Steel AISI M2 was studied, with diameter of 10 mm, uncoated and coated with silicon dioxide (SiO2) by the sol-gel method and titanium nitride (TiN) by PVD process in the drilling of nodular cast iron. The SiO2 coating had thicknesses of 390 to 500 nm, the TiN coating had thicknesses of 3,4 to 3,9 µm. In the pin on disk test, the highest friction coefficient and wear rate were for the uncoated tool, obtaining a severe abrasive wear; the SiO2 coated pin showed the best performance up to the 55 m/min sliding speed characterizing a mild abrasive wear. The TiN coated pin showed lower friction coefficients and wear rates for all speeds of slipping indicating mild abrasive wear. Regarding the drilling test, the statistical analysis were applied totalizing in 54 tests for the data of feed force, roughness and average diameter. The roughness error was evaluated graphically. The results indicated that the feed force was higher for the uncoated tool. In relation to the average roughness (Ra) and the mean diameter, the increase of the feed contributed to increase Ra, but when it comes to the diameter, the smaller dimensional variations of the holes were for the higher feed. Regarding the tool, the coatings influenced to lower values of Ra and of average diameter. As for the roughness error, it was observed that the coated tools provided decreasing errors. About the burr, the cutting parameters - cutting speed 40 m/min and 55 m/min, feed 0.25 mm/rev. -presented uniform burrs for the uncoated and SiO2 coated tool. The TiN tool showed uniform burrs for most holes. In relation to the shape of the chips, the increase of cutting speed and feed reduced the size of the chip, without changing the type. A final evaluation regarding on the wear test, the coated tools obtained lower mean and maximum flank wear values, but it was not possible to evaluate the wear mechanisms due to the adherence of material present in the drills.